Do individual short-sellers make money? Evidence from Korea - Wang, Shu-Feng; Lee, Kuan-Hui; Woo, Min-Cheol (Journal of Banking & Finance, 2017)
We use a proprietary trade- and account-level dataset of short sales to investigate the profitability of individual investors short-selling in the Korean stock market from August 1, 2007, to May 31, 2010. Using actual data on short-covering transactions, we find that the average profit is 26,810 Korean won (roughly USD 24.4) per trade per hour, and about 44% of shorted trades are covered within a day. We also find that the profitability of short-selling decreases as the hours-to-cover increases. Account-level analyses show that investors who sell short more firms make higher profits than those who sell short fewer firms and that the profitability of short-selling is persistent. We attribute the profitability to short-sellers’ ability to exploit short-run price reversals and information processing skills.